PEMBINAAN DAN PENDAMPINGAN KAMPOENG KAJOE TANGAN HERITAGE MALANG - Dwi Nita Aryani; Nunung Nurastuti Utami; Setyawan Setyawan; Ali Lating; Triana Murtiningtyas (Jurnal Pengabdian kepada Masyarakat, 2020)
illage in the Kauman area, Kec. Klojen, Malang City, is known as Kampoeng Kajoe Tangan (KJT) heritage because it has many ancient and unique buildings, but currently it is not widely known to the public. The KJT must be managed by a solid team of administrators in order to provide added value to the village and its citizens. Visits and interviews with the management team were carried out to see the atmosphere of the village in the past and to find out the role of the management team. So far, the division of tasks and responsibilities within the team has become a problem, resulting in overlapping, resulting in ineffective implementation of plans and activities. Lack of promotion because it does not have a marketing department causes less exposure of buildings that can be visited. Making job descriptions and adding a marketing section, encourages more effective work, more attractive promotions so that they can be better known and attract the public